Pain free dental services through compassion - Ismail, Izzati Nabilah Ismail; Muhamad Halil, Mohd Haikal (SULTAN AHMAD SHAH MEDICAL CENTRE @ IIUM, 2024)
This chapter explores the role of compassion in delivering pain-free dental services and improving patient experiences in dental care. It highlights how pain perception is influenced not only by clinical procedures but also by psychological, emotional, and interpersonal factors. Through compassionate communication, empathy, and patient-centred approaches, dental professionals can reduce anxiety, fear, and perceived pain among patients. The chapter discusses practical strategies such as active listening, clear explanations, reassurance, and respect for patient autonomy to enhance comfort during dental treatment. It further emphasizes the importance of creating a supportive clinical environment that fosters trust, cooperation, and long-term patient engagement. By integrating clinical competence with compassion, this chapter advocates a holistic approach to dentistry that promotes patient well-being, dignity, and improved oral health outcomes.